Characterization of Tropical Rural Homegardens and Their Households in a Premontane Forest of Costa Rica - Arias Ramírez, Jessica (2026)
Introduction: Homegardens are mixed cropping systems near homes that contribute Food and Nutritional Security (FNS), agrobiodiversity conservation, and household resilience. Yet, scientific studies in Central America, and particularly in Costa Rica, are still limited, and traditional knowledge about these systems is gradually disappearing. This study characterizes homegardens and their households in San Luis, Monteverde, a community undergoing socio-economic changes due to tourism and gentrification. Methodology: Following a descriptive and exploratory research approach, 23 homegardens (15 in Alto San Luis and 8 in Bajo San Luis) were selected using purposive sampling strategy with criterion-based selection. Data collection involved structured questionnaires, interviews, and direct observations. Descriptive statistics and correlation tests explored links between species richness and household variables. Results: A total of 182 species (169 plants, 13 animals) from 65 taxonomic families were recorded. Bajo San Luis, farther from markets and closer to forests, showed greater species diversity. Homegarden owners were mostly women (87%), with an average age of 54 years, and most had only completed primary education. Household size was small (3 members), and older age correlated with higher species richness (r = .67, p < .001). Most gardens were maintained for self-consumption. Conclusions: Homegardens in San Luis support agrobiodiversity, food security, and community health. Their maintenance is deeply linked to women’s roles and traditional knowledge of older adults. However, threats such as youth migration, urbanization, and generational gaps challenge their sustainability. Policies should promote knowledge transfer, recognize health and dietary contributions, and support these spaces as vital components of local food systems.